مساهمة القطاع المالي في النمو الاقتصادي للجزائر باستخدام نماذج ARDL (Revue El-Wahat pour les Recherches et les Etudes, 2021)
This Study Aimed To Analyses, The Impact Of The Financial Sector On Economic Growth In ‎Algeria During The Period 1980-2014. Two Models Were Adopted To Reflect The ‎Relationship Between The Two Variables; The First Model Contains A Direct Index, Of ‎Financial Development In Algeria. In The Second Model. Financial Development Was ‎Expressed Through Two Indicators: One Measuring Institutional Development, And The ‎Second Measuring The Development Of The Financial Market. The Study Data Was ‎Obtained From The World Bank And IMF Databases‏.‏The Study Reached. The Inability To Rely On The First Model, To Study The Relationship ‎Between The Two Variables In The Long Term. The Results Of The Bound Test Showed The Possibility To Use The Second Model, To Analyze The Long-Term Relationship. ‎After Estimating Its Coefficients. Using The ARDL Model. The Results In The Long Term. ‎Show A Positive Relationship. Between The Index Of Institutional Development And ‎Economic Growth. While The Relationship Was Negative And Weak, Between The ‎Financial Market Performance And Economic Growth‏.‏‏ Keywords-  Financial Development, Economic Growth, Supply-Leading Approach, Demand-Following Approach.